Pengaruh Jenis Kacang Kedelai Dalam Proses Fermentasi Pada Pembuatan Kecap Manis - Vira Ananda Agustin; Ayu Dwi Nursanti; Mujahidah Mutiara Robbani; Sheren Kunti Setyowati; Liss Dyah Dewi A (STIKes Ibnu Sina Ajibarang, 2024)
Soy sauce is an additional seasoning that has been known since the era of 300 years BC (SM), soybeans are the main ingredient in making sweet soy sauce. This research uses three types of soybeans with different quality, namely medium and low high quality. Each type of soybean is processed using the same fermentation method to produce soy sauce. The elements analyzed can amount of acidity, protein content, water, and the taste of soy sauce produced. The observation results stated that high-quality soybeans produce soy sauce with higher protein levels, optimal acidity levels, and better taste compared to medium and low-quality soybeans. Low-quality soybeans produce soy sauce with lower protein levels and a less-than-preferred flavor. In conclusion, the quality of soybeans has a very significant influence on the quality of soy sauce produced, so the selection of high quality soybeans is highly recommended in the soy sauce production stage to produce the best quality products.